(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To develop and validate a novel, precise, and accurate Reverse-Phase High-Performance Liquid Chromatographic (RP-HPLC) method for the simultaneous estimation of Empagliflozin (EMPA) and Gliclazide (GLZ) in a combined tablet dosage form. Methods: The chromatographic separation was optimized on aa Purospher® STAR C18 column (250 mm × 4.6 mm, 5 µm) using an isocratic mobile phase comprising 0.05 M potassium dihydrogena phosphate buffer (pH adjusted to 3.6 with orthophosphoric acid) and acetonitrile in the ratio of 62:38 (v/v). The flow rate was maintained at 1.1 mL/min, and detection was carried out at 225 nm using a photodiode array (PDA) detector. The method was rigorously validated as per the International Council for Harmonisation (ICH) Q2(R1) guidelines. Results: The retention times for GLZ and EMPA were found to be 4.12 ± 0.03 min and 6.95 ± 0.05 min, respectively, with a total analysis time of 10 minutes. The method demonstrated excellent linearity in thea concentration ranges of 16–160 µg/mL for GLZ (r² = 0.9996) and 3.2–32 µg/mL for EMPA (r² = 0.9995). The mean percentage recoveries for GLZ and EMPA were 99.84% and 100.23%, respectively, confirming higha accuracy. The method was also found to be precise, specific, robust, and sensitive, with limits of detection (LOD) of 0.38 µg/mL and 0.07 µg/mL, and limits of quantification (LOQ) of 1.15 µg/mL and 0.21 µg/mL for GLZ and EMPA, respectively. Conclusion: The proposed RP-HPLC method is simple, rapid, reliable, and well-suited for the routine quality control and simultaneous quantitative analysis of Empagliflozin and Gliclazide in combined pharmaceutical formulations.